Use of continuous glucose monitoring in non-intensively managed type 2 diabetes: a Saudi Arabian consensus - Almehthel, Mohammed; Al-Saeed, Abdulghani; Al-Sabaan, Fahad; Al-Malky, Faisal; Zarif, Hawazen; Al-Zubaidi, Lamya; Al-Sofiani, Mohammed E.; Abdulaal, Omar; Al Argan, Reem; Al Sifri, Saud; Al-Harbi, Turki; Aldahash, Raed (Frontiers in Endocrinology, 2026)
BackgroundSaudi Arabia has one of the highest prevalences of diabetes globally, with 16.4% of the population living with type 2 diabetes (T2D). While continuous glucose monitoring (CGM) is widely used for patients with type 1 diabetes, evidence suggests its benefits can extend to patients with T2D. The aim of this Delphi consensus was to provide a framework for the use of CGM in patients with T2D who are non-intensively managed in Saudi Arabia.MethodsAn expert panel of ten adult endocrinology physicians, one internal medicine and diabetology specialist, and one family medicine physician was formed. Consensus generation was undertaken using Delphi methodology; a face-to-face expert meeting and literature review formed the basis of preliminary statements, which were further refined by the panel. Two rounds of voting were used to confirm the level of agreement to each statement.ResultsConsensus was reached on 27 statements relating to the use of CGM in non-intensively managed T2D. Recommended patient profiles for continuous and intermittent use of CGM are provided, alongside general principles of CGM use and background statements.ConclusionsThis consensus provides recommendations and summarizes local and international evidence as well as expert opinion regarding CGM use in patients with T2D. To expand the use of CGM into the wider population of T2D in Saudi Arabia and enable these individuals to benefit from the technology, a shift in healthcare services, education, and attitudes across the country is necessary.